The conscience wars: rethinking the balance between religion, identity, and equality - Mancini, Susanna ca. 20./21. Jh.; Rosenfeld, Michel (Cambridge University Press, 2018)
"In this work, Professors Rosenfeld and Mancini have brought together an impressive group of authors to provide a comprehensive analysis on the greater demand for religions exemptions to government mandates. Traditional religious conscientious objection cases, such as refusal to salute the flag or to serve in the military during war, had a diffused effect throughout society. In sharp contrast, these authors argue that today's most notorious objections impinge on the rights of others, targeting practices like abortion, LGTBQ adoption, and same-sex marriage. The dramatic expansion of conscientious objection claims have revolutionized the battle between religious traditionalists and secular civil libertarians, raising novel political, legal, constitutional and philosophical challenges. Highlighting the intersection between conscientious objections, religious liberty, and the equality of women and sexual minorities, this volume showcases this political debate and the principal jurisprudence from different parts of the world and emphasizes the little known international social movements that compete globally to alter the debate's terms"--